PENGETAHUAN DAN SIKAP ORANG DEWASA ANGGOTA GEREJA EBEN HAEZER TERHADAP COVID 19 - Oktorida Maddalena Sitorus; Mori Peranginangin (Jurnal Skolastik Keperawatan, 2020)
The COVID 19 pandemic has infected 215 countries in the world, including Indonesia. The number of Indonesian society who have contracted Covid 19 is increasing day by day and the death rate is continuing to increase as well . Currently, it is very important to have knowledge about Covid 19 and have an appropriate behaviour to break the chain of transmission of Covid 19. The purpose of this study is to determine the level of knowledge and behaviour of adult members in GMAHK Eben Haezer towards Covid 19. This study used a descriptive quantitative method. The sample of 34 respondents was taken using simple random sampling technique. The instrument used is a questionnaire consisting of nine questions to assess the level of knowledge, and four questions to assess behaviour based on Wijayanti's et al (2020). The data was collected using google form from 26 October - 27 November 2020. The results of univariate analysis show that the level of knowledge of adults members in Eben Haezer related to covid 19 is in the moderate category (69.7%) and the attitude is also in the fairly good category (78.8%). Various efforts need to be made to increase public knowledge and behaviour in relation to Covid 19. Keywords: Attitude, Covid-19, Knowledge.